A ressignificação da prática pedagógica na educação a distância on-line - Menezes, Ligia Cristina Rubim (2004)
The aim of this research is finding indicators of educational conceptions that can contribute to a new meaning for pedagogical practices in on-line distance learning and elements that can help to envision ways encompassed with the demands of current reality, fostered by technological, epistemological, educational and social changes Due to increasing investments in on-line distance learning in Brazil, it is important to carry out researches that contribute to the development of perspectives of formation that help to overcome a view that is individualist, out of context, static, based in transmission of information, and homogenizes knowledge. Presenting traces of a new meant pedagogical practice, the course Educação a distdncia na prática, offered by Coordenadoria Geral de Especialização, Aperfeiçoamento e Extensão COGEAE, by PUC-SP, through an virtual environment of learning, it is used as base for reflections in this work. In the body of this work, it is taken place a dialogue between data and concepts, resulted from the movement between them. The interaction among the elements built the course, which searches to understand these elements into their relationship with knowledge, technology, and education, starting from the articulation of the theoretical base of Edgar Morin, Pierre Lévy and Paulo Freire, respectively. The elements found in the course horizontal hierarchy and decentralization, autonomy, context, and non-linearity - allow a new meaning about on-line distance learning concerning to the pedagogical relationship between its participants, to their changing roles, to the relationship with knowledge, to the curriculum movement, and, also, to the new meaning of technology. It is important to consider, however, that beyond the possibilities shown, it is also presented challenges to be faced in proposing such pedagogical practice